Using The Demirjian Method For Estimating The Dental Age Of Children In Surabaya, Indonesia - Beshlina Fitri Widayanti Roosyanto Prakoeswa; Arofi Kurniawan; An’nisaa Chusida; Beta Novia Rizk; Anugerah I’zaaz Darmawan; Andini Kamilia Nur Aisyah; Aspalilah Alias (Universitas Airlangga, 2024)
Indexed by Scopus